Non-financial benefits of CSR: An empirical study - Galbreath, Jeremy (Curtin University of Technology, 2007)
CSR has been found to positively affect the financial success of firms. However, firm success is multidimensional, reflecting dimensions beyond just the financial. This paper sought to understand the role that CSR plays in affecting non-financial dimensions of firm success. Specifically, a link between CSR and three important non-financial measurements were studied. The findings are provocative. By studying a heterogeneous sample of firms, the data provided strong support for the hypothesized relationships; namely, CSR was found to lower employee turnover while positively affecting both customer satisfaction and firm reputation. These results confirm theory, in that CSR is as an activity that can help to meet the justice needs of employees while demonstrating equity and signaling positive impressions to external stakeholders